Does Benefit Receipt Affect Future Income? An Econometric Explanation - Dean Hyslop (New Zealand Government, The Treasury, 2000)
This paper provides an econometric analysis of the effects of receiving welfare benefits on individuals' future income, using longitudinal administrative data on individual incomes. After controlling for heterogeneous differences in individual incomes, spurious effects of contemporaneous benefit receipt and possible endogeneity with incomes, there is no systematic evidence of a positive or negative effect of benefit receipt on incomes. The results are generally imprecisely estimated and sensitive to the choice of specification. Also, a simple first-order specification with unobserved heterogeneity provides a reasonable characterisation of individual income dynamics, although formal statistical tests tend to reject this specification as being too parsimonious.
Keywords: 330